iVAC-XS15-CLL01: personalized multi-peptide vaccination in combination with the TLR1/2 ligand XS15 in CLL patients undergoing BTK-inhibitor-based regimens - Englisch, Alexander; Hayn, Clara; Jung, Susanne; Heitmann, Jonas S.; Hackenbruch, Christopher; Maringer, Yacine; Nelde, Annika; Wacker, Marcel; Denk, Monika; Zieschang, Lisa; Kammer, Christine; Martus, Peter; et al. (Frontiers in Oncology, 2024)
Chronic lymphocytic leukemia (CLL) is the most common form of leukemia among adults in Western countries. Despite the introduction of targeted therapies, including first-line Bruton's tyrosine kinase inhibitor (BTKi) treatment, CLL remains largely incurable. Frequent disease relapses occur due to remaining treatment-resistant CLL cells, calling for novel therapies to eliminate minimal residual disease (MRD). Peptide-based vaccination targeting human leucocyte antigen (HLA)-presented CLLassociated antigens represents a promising, low-side-effect therapeutic option to optimize treatment responses and eliminate residual tumor cells by inducing an anti-leukemic immune response. The iVAC-XS15-CLL01 trial is an open-label, first-in-human (FIH) Phase I trial, evaluating the CLL-VAC-XS15 vaccine in CLL patients undergoing BTKi-based therapy. The vaccine was developed from HLA-presented CLL-associated antigen peptides, identified through comparative mass-spectrometrybased immunopeptidome analyses of CLL versus healthy samples in a previous study. To facilitate rapid and cost-effective deployment, vaccine peptides are selected for each patient from a premanufactured "peptide warehouse" based on the patient's individual HLA allotype and CLL immunopeptidome. The trial enrolls 20 CLL patients, who receive up to three doses of the vaccine, adjuvanted with the toll-like-receptor (TLR) 1/2 ligand XS15 and emulsified in Montanide ISA 51 VG. The primary objective of the iVAC-XS15-CLL01 trial is to assess the safety and immunogenicity of the CLL-VAC-XS15 vaccine. Secondary objectives are to evaluate the vaccine impact on MRD, progression-free survival, and overall survival, as well as comprehensive immunophenotyping to characterize vaccine-induced T-cell responses. This Phase I trial aims to advance CLL treatment by enhancing immune-mediated disease clearance and guiding the design of subsequent Phase II/III trials to implement a new therapeutic strategy for CLL patients. This trial was registered on clinicaltrials.gov (NCT04688385, 12/2020).